Realistic Utopianism and Alternatives to Imprisonment:The ideology of crime and the utopia of harm - Copson, Lynne (2016)
Although the harms and inadequacies of the criminal justice and penal systems are well-documented, the contemporary impulse is largely one born in critique.Currently, it seems that as critical scholars, activists, and citizens, we are far better at deconstruction than positive construction of meaningful alternatives.Even where evidence of an impulse toward the latter exists, this is often diluted over time via its translation into routine politics.Whilst, in many ways, understandable (given the contemporary climate of knowledge-production which eschews ‘radical’ reform as hopeless and idealistic and/or inherently dangerous, and where the politics of knowledge production sees an endless tension between political independence and irrelevance on the part of those working in this field), this article explores the question of how, given this climate, we might begin to move beyond critique, towards the development of radical, yet realistic, meaningful alternatives to punitive penal practices.Despite attempts to develop realistic alternatives within criminology and penology, through a burgeoning interest in the concept of utopia as a form of praxis, the central argument put forward here is that responding differently to crime begins by thinking differently about crime.Drawing on Mannheim’s distinction between ideology and utopia, it offers the discourse of social harm as an important means of encouraging us to think differently and respond differently to social problems.It is argued that, so long as we take the criminal justice system as the starting point of our critique and the locus for the construction of alternatives, reforms are destined to reinforce and legitimise the contemporary ‘regime of truth’ and dominant constructions of crime, harm and justice. Therefore, it is only through the adoption of a ‘replacement discourse’ of harm that we can start to build realistic utopias and meaningful alternatives to imprisonment